2021
DOI: 10.1111/imcb.12477
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of microRNA in regulating the mTOR signaling pathway in immune and inflammatory responses

Abstract: The mechanistic/mammalian target of rapamycin (mTOR) is considered to be an atypical protein kinase that plays a critical role in integrating different cellular and environmental inputs in the form of growth factors, nutrients and energy and, subsequently, in regulating different cellular events, including cell metabolism, survival, homeostasis, growth and cellular differentiation. Immunologically, mTOR is a critical regulator of immune function through integrating numerous signals from the immune microenviron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 136 publications
(164 reference statements)
2
25
0
Order By: Relevance
“…mTOR signaling is a key regulator of immune cell metabolism and function. It acts as a part of two structurally and functionally distinct signaling complexes, mTORC1 and mTORC2 (mTOR complexes 1 and 2) [55] . mTORC2 signaling is required for the generation of M2 macrophages [56] .…”
Section: Resultsmentioning
confidence: 99%
“…mTOR signaling is a key regulator of immune cell metabolism and function. It acts as a part of two structurally and functionally distinct signaling complexes, mTORC1 and mTORC2 (mTOR complexes 1 and 2) [55] . mTORC2 signaling is required for the generation of M2 macrophages [56] .…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxiainduced tumor exosomes containing let-7a microRNA (miRNA) enhance mitochondrial OXPHOS activity and suppress insulin/Akt/ mTOR signaling pathway in bone marrow-derived macrophages (BMMs), as a result, promotes polarization of infiltrating macrophages to an M2-like phenotype. Therefore, biomoleculeloaded exosomes, such as let-7a, enhance tumor immune evasion and tumor progression by promoting changes in immunometabolic profile of infiltrating monocyte-macrophage population (Figure 3) (2,142). miR-100 is highly expressed in TAMs and promotes M2polarization of macrophages, and maintains TAMs phenotype through the downregulation of the mTOR signaling pathway.…”
Section: Mtor Pathway Mediates Polarization Of Tumor-associated Macro...mentioning
confidence: 99%
“…The mammalian target of rapamycin (mTOR; now officially known as the mechanistic target of rapamycin) is a ubiquitous serine/threonine-specific protein kinase, plays a critical role in regulating numerous cellular functions, including cell growth, proliferation, survival, protein synthesis, ribosome biogenesis, autophagy, and metabolism (1,2). mTOR functions within two functionally and structurally distinct multi-component kinase complexes called mTOR complex 1 (mTORC1) and mTOR complex 2 (mTORC2) that act as the central nodes of the phosphoinositide 3-kinase (PI3K)/Akt downstream signaling pathway (3).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that mTOR could regulate tumor immunity through modulating the interactions between the stroma and the tumor, thus possibly promote carcinogenesis (Guri, Nordmann & Roszik, 2018;Irelli et al, 2019). mTOR not only regulated the innate and adaptive immune response through modulating the effector response of innate immune cells such as macrophage, DCs, neutrophils and NKs, but also played a prerequisite role in the development of adaptive immune cells, such as CD4+ T, CD8+ T, Tregs and B cells (Nazari et al, 2021). The underlying mechanism behind the association of mTOR expression and immune cells has not been clearly illustrated.…”
Section: Discussionmentioning
confidence: 99%